Financial control systems and their evolution in Ecuador - Granda Aguilar, Victor (2018)
Considering the current holistic character of the technical-financial and administrative extern control system of the public resources management present in doctrine, legislation and international instruments, this article analyzes the main control systems that can be identified at international level: Court of Auditors and General Comptroller. In this context, this article studies the evolution of the Ecuadorian system of control from the beginnings of the Republic to the present, showing the historical backward that the legal amendments promoted by the President Rafael Correa and the constitutional amendments approved by the National Assembly in December, 2015, represent because of the elimination of some powers of the General Comptroler´s Office, especially in order to determine responsibilities on the management of public resources.